2022
DOI: 10.3390/plants11030306
|View full text |Cite
|
Sign up to set email alerts
|

Innovating the Synergistic Assets of β-Amino Butyric Acid (BABA) and Selenium Nanoparticles (SeNPs) in Improving the Growth, Nitrogen Metabolism, Biological Activities, and Nutritive Value of Medicago interexta Sprouts

Abstract: In view of the wide traditional uses of legume sprouts, several strategies have been approved to improve their growth, bioactivity, and nutritive values. In this regard, the present study aimed at investigating how priming with selenium nanoparticles (SeNPs, 25 mg L−1) enhanced the effects of β-amino butyric acid (BABA, 30 mM) on the growth, physiology, nitrogen metabolism, and bioactive metabolites of Medicago interexta sprouts. The results have shown that the growth and photosynthesis of M. interexta sprouts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…In the previous study on hairy root cultures of S. miltiorrhiza, it was described that BABA added at higher dosages (1 mM) resulted in slight root growth suppression, although this effect was not observed when BABA was used in combination with MeJA, which is in accordance with the results of the present study [11]. In the other study, it was demonstrated that BABA stimulated the photosynthesis and growth of Medicago interexta sprouts, to a higher extent when applied together with selenium nanoparticles (SeNPs) [30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the previous study on hairy root cultures of S. miltiorrhiza, it was described that BABA added at higher dosages (1 mM) resulted in slight root growth suppression, although this effect was not observed when BABA was used in combination with MeJA, which is in accordance with the results of the present study [11]. In the other study, it was demonstrated that BABA stimulated the photosynthesis and growth of Medicago interexta sprouts, to a higher extent when applied together with selenium nanoparticles (SeNPs) [30].…”
Section: Discussionsupporting
confidence: 92%
“…Previously, the importance of preincubation with BABA on the tanshinone total yield was described in S. miltiorrhiza hairy root cultures, and the authors pointed out that tanshinone productivity increased steadily with the prolongation of BABA treatment [38]. Further, it was demonstrated that BABA influenced results, especially in combination with SeNPs' potentiated accumulation of phenolics and flavonoids, and especially when they were applied together [30]. Next, the stronger activation of defence response was observed in BABA-primed mango fruit to subsequent inoculation with Colletotrichum gloeosporoides [39].…”
Section: Discussionmentioning
confidence: 99%
“…Folin–Ciocalteu and aluminum chloride calorimetric assays were used to measure the contents of polyphenols and flavonoids, as fully described by Zhang et al and AbdElgawad et al, respectively. Total antioxidant capacity (TAC) was quantified through the ferric-reducing antioxidant power method using Trolox as a reference base . Tocopherol content was measured using HPLC, in which Dimethyl tocol was used as an internal standard .…”
Section: Methodsmentioning
confidence: 99%
“…The gradient elution program was as follows: 82% to 80% B (v/v) in 5 min, to 60% B at 12 min and finally to 82% B at 20 min. The injection volume for all samples was 20 μL [20] . The phenolic compounds were analyzed by matching the retention time and their spectral characteristics against those of standards.…”
Section: Hplc Analysismentioning
confidence: 99%